The Influence of Customer Trust and Digital Payment Methods on Purchasing Decisions at PT Bilah Baja Makmur Abadi - Vanessa Valantis; Desma Erica Maryati Manik (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2024)
The aim of this research is to analyze the influence of customer trust and digital payment methods on purchasing decisions at PT Bilah Baja Makmur Abadi. The research method in this research is a quantitative research method using a questionnaire as a data collection technique. The sample in this study used the Slovin formula and obtained 77 respondents. The results of the research using multiple linear regression analysis obtained Purchase Decision results = 9.284 + 0.442 Customer Trust + 0.259 Digital Payment Method + e. Partially, Customer Trust has a value of tcount (3.834) > ttable (1.992) and a significant value of 0.000 < 0.05, so it can be concluded that there is a partially significant positive influence on Customer Trust on Purchasing Decisions at PT Bilah Baja Makmur Abadi. Partially, the Digital Payment Method shows that the value of tcount (2.151) > ttable (1.992) with a significant level of 0.035 <0.05 so it can be concluded that there is a partially significant positive influence between the Digital Payment Method on Purchasing Decisions at PT Bilah Baja Makmur Abadi. Simultaneously it has a value of Fcount (35.476) > Ftable (3.12) with a significance of 0.000 < 0.05 so it can be concluded that there is a significant influence between Customer Trust and Digital Payment Methods on Purchasing Decisions at PT Bilah Baja Makmur Abadi. The results of the coefficient of determination show that purchasing decisions are influenced by customer trust and payment methods by 48.9% while the remaining 51.1% is influenced by other factors originating from outside this research model such as product quality and brand image.